1977
DOI: 10.1136/hrt.39.8.914
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis as a manifestation of Chlamydia B infection (psittacosis).

Abstract: A case of Chlamydia B (psittacosis) endocarditis is described in a patient with no known previous valve disease. After mitral valve replacement a fall in Chlamydia B antibody titre occurred. At repeat mitral valve replacement five months later for a paravalve leak no evidence of continuing endocarditis was present. Direct confirmation of infection in the patient's apparently healthy budgerigar was obtained. Aspects of the pathogenesis, diagnosis, and treatment are discussed.Endocarditis caused by Chlamydia B i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…was probably the etiologic agent. Of the 15 remaining patients previously reported as suffering from Chlamydia endocarditis, C. psittaci was considered the etiologic agent in 11 patients (3,7,8,18,19,21,25,30,38,39), C. trachomatis was considered the etiologic agent in 2 patients (6, 37), C. pneumoniae was considered the etiologic agent in 2 patients (10,26), and identification to the species level was not available for the etiologic agent in 1 patient (15). Chlamydia endocarditis and Bartonella endocarditis share clinical and epidemiological features, including a predominant involvement of males, no previous cardiac valve damage, more frequent involvement of aortic valves, diagnostic delay due to the difficulty in culturing the microorganisms, frequent relapses despite adequate antibiotic therapy, extensive valve damage, and the necessity of valve replacement for cure.…”
Section: Discussionmentioning
confidence: 99%
“…was probably the etiologic agent. Of the 15 remaining patients previously reported as suffering from Chlamydia endocarditis, C. psittaci was considered the etiologic agent in 11 patients (3,7,8,18,19,21,25,30,38,39), C. trachomatis was considered the etiologic agent in 2 patients (6, 37), C. pneumoniae was considered the etiologic agent in 2 patients (10,26), and identification to the species level was not available for the etiologic agent in 1 patient (15). Chlamydia endocarditis and Bartonella endocarditis share clinical and epidemiological features, including a predominant involvement of males, no previous cardiac valve damage, more frequent involvement of aortic valves, diagnostic delay due to the difficulty in culturing the microorganisms, frequent relapses despite adequate antibiotic therapy, extensive valve damage, and the necessity of valve replacement for cure.…”
Section: Discussionmentioning
confidence: 99%
“…(239)(240)(241)(242)(243) The diagnosis is usually established postmortem or at operation to replace a perforated valve, but very rarely a positive serology leads to the correct diagnosis earlier in the evolution of the disease. (240) The disease can attack normal heart valves, and it is doubtful whether tetracycline alone (even for several months) is sufficient to eliminate the microorganism from an endocardial vegetation. Current thoughts are that the patient should remain on tetracycline(?…”
Section: Chlamydiaementioning
confidence: 99%
“…Chlamydia spp. have often been suggested to be causative agents of endocarditis (18,24,60,61,89,132,136,156,201,231,253,285,291,295 19:1054, 1990). However, in a recent review of 10 patients reported to have chlamydial endocarditis, 8 were finally diagnosed with Bartonella endocarditis after their sera were tested by antibody cross-absorption and Western immunobloting (176,225).…”
Section: ͻ150 ϫ 10mentioning
confidence: 99%